The Adventures of Beekle : The Unimaginary Friend - Santat, Dan (New York : Little, Brown and Company, 2019)
"When an imaginary friends overlooked by all the real children looking for companions, he sets off on an incredible journey to meet his perfect match." --Page 4 of cover.
"This special edition was printed for Kohls Department Stores, Inc. (for distribution on behalf of Kohls Cares, LLC, its wholly owned subsidiary) by Little, Brown Books for Young Readers."
Keywords: Imaginary companions; Juvenile fiction; Friendship -- Juvenile fiction; Childrens stories; Picture books; Fiction; Juvenile works; Fiction